If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -25 = 11x + -5 + 2C Reorder the terms: -25 + 3x = 11x + -5 + 2C Reorder the terms: -25 + 3x = -5 + 2C + 11x Solving -25 + 3x = -5 + 2C + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -25 + 3x + -11x = -5 + 2C + 11x + -11x Combine like terms: 3x + -11x = -8x -25 + -8x = -5 + 2C + 11x + -11x Combine like terms: 11x + -11x = 0 -25 + -8x = -5 + 2C + 0 -25 + -8x = -5 + 2C Add '25' to each side of the equation. -25 + 25 + -8x = -5 + 25 + 2C Combine like terms: -25 + 25 = 0 0 + -8x = -5 + 25 + 2C -8x = -5 + 25 + 2C Combine like terms: -5 + 25 = 20 -8x = 20 + 2C Divide each side by '-8'. x = -2.5 + -0.25C Simplifying x = -2.5 + -0.25C
| 8(x+5)+8=4x+2 | | 96a+4b=4 | | 5(-9+3y)-2y=7 | | 14=6y+y | | (x-5)(2x+8)= | | 3(6+5y)=-2(-5+4y) | | 216x-162=18(12x-9) | | 31.2p=65.1 | | (3x-24)+2x=2x | | 6(1/2u-2/3) | | 1/2x^2-6=0 | | 7x-3(3x+17)=-37 | | 2x-2+x=x-24 | | Cot/cos=CDC | | -9x-3y=7 | | 10x+26x-10=9(4x+10) | | 3(4-6y)+7=-1 | | M/9--213=231 | | 12.1=p+2.3 | | X-(156-X)=78 | | 3x-24+2x=2x | | 38x+85=38x+78 | | x2=49/81 | | 5x+4(-3x-10)=103 | | 3/4(2x–8) | | X/-1/6=6/7 | | x^2+4x-8y+12=0 | | -5(f-929)=85 | | P+2p+3p+2=2 | | 7x+23x-4=6(5x+9) | | 18(w+25)=468 | | 4x-2(1+2x)=6 |